ENGLISH LANGUAGE IN INDIA - Bedi, Jaskiran. ([S.l.])
1 online resource
Keywords: This book examines the relationship between the English language and growth - economic and inclusive - in India. It explores why English continues to be the language of aspiration long after Independence. With the second largest English-speaking population in the world today, India is testimonial to how a linguistic legacy continues to cast a long shadow on its contemporary discourse in the economic arena. The volume: Explores how English language proficiency constitutes as human capital. Draws in the latest India Human Development Survey data. Investigates the relationship between the language and economic indicators such as wages, household income and state growth. Purther investigates the role of English language in the inclusivity of growth. Provides a snapshot of the pedagogy of English in the Indian education system. First of its kind in scope, this volume will be of great interest to scholars of economics, education, sociolinguistics, development studies, politics and sociology. It will also be of great interest to the general reader.